2012
DOI: 10.1007/8904_2012_130
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for Lysosomal Storage Disorders in Hungary

Abstract: Even though lysosomal storage disorders (LSDs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 46 publications
3
67
0
2
Order By: Relevance
“…Newborn screening studies in Europe and in Taiwan revealed a significantly higher prevalence of FD (as high as 1 in 1250) than was expected based on previous calculations 8–11 76 77. In two Taiwanese studies, 100/120 (83%) identified individuals showed an intronic variance of uncertain significance, IVS4+919G>A. Hwu et al demonstrated 3.6–28.5% residual leukocyte enzyme activity in men 10.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Newborn screening studies in Europe and in Taiwan revealed a significantly higher prevalence of FD (as high as 1 in 1250) than was expected based on previous calculations 8–11 76 77. In two Taiwanese studies, 100/120 (83%) identified individuals showed an intronic variance of uncertain significance, IVS4+919G>A. Hwu et al demonstrated 3.6–28.5% residual leukocyte enzyme activity in men 10.…”
Section: Discussionmentioning
confidence: 86%
“…Two studies that were labelled as ‘other’ were performed in persons with migraine, and premature atherosclerotic males, respectively 74 75. Six studies on newborn screening were included 8–11 76 77…”
Section: Resultsmentioning
confidence: 99%
“…25,26 The switch to MS/MS was possible because, in collaboration with Chamoles, Michael Gelb, C. Ronald Scott, and others developed enzyme-specific substrates, synthesized isotopically labeled substrates, and measured the products of various enzyme reactions simultaneously in DBS with MS/ MS. 27 Since the first description of their Flow Injection Analysis (FIA) MS/MS assay, modifications including the number of enzymes, sample preparation steps, and the addition of liquid chromatography (LC) have been reported and applied in both limited studies and routine NBS. [28][29][30][31][32][33][34][35][36][37][38][39] Another analytical multiplex approach to NBS for LSDs, also based on Chamoles' fluorometric enzyme activity assays, was developed by Advanced Liquid Logic, Inc. (ALL; now called Baebies Inc.). 40 Their procedure has the ability to simultaneously perform up to 5 different enzyme assays on a single DBS.…”
Section: Newborn Screening Assays For Lsdsmentioning
confidence: 99%
“…In addition to live screening, there have been multiple reports of retrospective pilot studies to screen for LSDs [29][30][31]. In these studies, samples that screen positive, biochemically, for a given LSD are genotyped.…”
Section: Missouri Lsd Screeningmentioning
confidence: 99%
“…However, we came to understand that infants with a common genotype containing the p.Thr112Ala mutation without p.Ile562Thr (legacy: p.Ile546Thr) in cis were not at risk for KD [38], and as of November, 2015 infants carrying this GALC variant were no longer referred [3]. Similarly, DNA testing for GAA mutations has identified a high number of cases with the p.Val222Met variant and this variant was reported at a fairly high frequency in retrospective screening of dried blood spots for Pompe disease in Hungary [29], yet there is no knowledge that this variant is disease-causing.…”
Section: Second-tier Molecular Testingmentioning
confidence: 99%